Design of a SCADA-Based Control System for Hybrid Power Generation Integrating a Screw Turbine and Solar Panels - Jonah Alfred Mekel; Franklin Bawano; Alfred Noufie Mekel; Tineke Saroinsong (Asosiasi Dosen Muda Indonesia, 2026)
The increasing demand for sustainable electricity requires hybrid renewable energy systems capable of improving power supply reliability and operational supervision under variable energy-source conditions. Purpose: This study aims to design and implement a laboratory-scale hybrid renewable energy control system integrating an Archimedes screw turbine and a photovoltaic system with PLC-based control and SCADA monitoring. Methodology: An experimental design and implementation approach was employed by integrating renewable energy generation, battery storage, electrical measurement devices, an industrial PLC, HMI, and cloud-based SCADA platform. Electrical voltage, current, power, energy, battery condition, and load status were acquired during laboratory testing and evaluated based on the functionality of monitoring, data logging, trend visualization, alarm notification, battery protection, and load control. Findings: The developed system successfully integrated renewable energy generation and industrial automation into a unified supervisory platform. The PLC continuously acquired electrical parameters, executed battery protection and load-switching logic, and communicated with the HMI and SCADA system. Real-time monitoring, historical data recording, graphical trend visualization, alarm notification, and remote load control operated successfully during experimental testing. Implications: The proposed architecture provides a practical platform for renewable energy monitoring, industrial automation education, and further development of automatic energy management and predictive supervision systems. Originality: Unlike previous studies that primarily focus on photovoltaic performance, Archimedes screw turbine optimization, or SCADA architecture separately, this study integrates photovoltaic generation, an Archimedes screw turbine, battery storage, industrial PLC control, HMI visualization, and cloud-based SCADA monitoring within a single laboratory-scale hybrid renewable energy platform.